Design, synthesis and biological evaluation of novel 2, 4-disubstituted quinazoline derivatives targeting H1975 cells via EGFR-PI3K signaling pathway. (1st August 2021) - Wang, Zhengjie; Liu, Limin; Dai, Honglin; Si, Xiaojie; Zhang, Luye; Li, Erdong; Yang, Zhang; Chao, Gao; Zheng, Jiaxin; Ke, Yu; Lihong, Shan; Zhang, Qiurong; et al.
Graphical abstract: Abstract: In order to find new and highly effective anti-tumor drugs with targeted therapeutic effects, a series of novel 4-aminoquinazoline derivatives containing N -phenylacetamide structure were designed, synthesized and evaluated for antitumor activity against four human cancer cell lines (H1975, PC-3, MDA-MB-231 and MGC-803) using MTT assay. The results showed that the compound 19e had the most potent antiproliferative activity against H1975, PC-3, MDA-MB-231 and MGC-803 cell lines. At the same time, compound 19e could significantly inhibit the colony formation and migration of H1975 cells. Compound 19e also arrested the H1975 cell cycle in the G1 phase and mediated cell apoptosis, promoted the accumulation of ROS in H1975 cells. Furthermore, compound 19e exerted antitumor effect in vitro by reducing the expression of anti-apoptotic protein Bcl-2 and increasing the pro-apoptotic protein Bax and p53. Mechanistically, compound 19e could significantly decreased the phosphorylation of EGFR and its downstream protein PI3K in H1975 cells. Which indicated that compound 19e targeted H1975 cell via interfering with EGFR-PI3K signaling pathway. Molecular docking showed that compound 19e could bind into the active pocket of EGFR. Those work suggested that compound 19e would have remarkable implications for further design of anti-tumor agents.